Africa Day Celebrations (Philology, 2023)
Africa Day is celebrated every year on May 25, across Africa and the world. It marks the day in 1963, when 32 African states came together to vote for the formation of the first union of African countries, the Organization of African Unity (OAU), which later evolved into the African Union (AU) (Edo & Olanrewaju, 2012).